The strategic options to enhance the competitive advantage of Malaysian restaurant sector - Yusr, Maha Mohammed; Mohd Mokhtar, Sany Sanuri; Salimon, Maruf Gbadebo; Perumal, Selvan (Universiti Teknikal Malaysia Melaka, 2018)
High competition in the market makes competitive advantage one of the absolute options that companies must seek to build and maintain competition. Organizational capabilities form one of the inimitable sources of competitive advantage. Therefore, establishing organizational capabilities is recognized as antecedents of competitive advantage. To build up such capabilities, several strategies have been applied. Thus, this study aims to investigate the role of IMO to enhance and build up the organizational capabilities and the competitive advantage. Hence, the present study to examine the direct effect of IMO on competitive advantage, the mediating role of organizational capabilities between IMO and competitive advantage. To do so, managers of restaurant chains sector were selected as the respondents from which the necessary data were collected.Partial least square was the statistical approach to get the result. The obtained results supported all the proposed hypotheses. Therefore, IMO is considered as one of the strategic options that organizations can apply to enhance their competitive advantage. Further discussion and suggestions for future studies were presented in the last section of the paper.